Physicochemical analysis of structural alteration and advanced glycation end products generation during glycation of H2A histone by 3‐deoxyglucosone. Issue 10 (7th November 2014) - Ashraf, Jalaluddin M.; Ahmad, Saheem; Rabbani, Gulam; Jan, Arif Tasleem; Lee, Eun Ju; Khan, Rizwan Hasan; Choi, Inho
Abstract Advanced glycation end‐products comprise a complex and heterogeneous group of compounds that have been implicated in diabetes‐related complications. The importance of the Maillard reaction is depicted by the formation of reactive intermediate products known as α‐oxoaldehydes, such as 3‐deoxyglucosone (3‐DG). This product has been found to be involved in accelerated vascular damage in diabetes. In the present study, calf thymus histone H2A was reacted with 3‐DG, and the generation of advanced glycation end products was investigated by determining the degree of side chain modifications (lysine and arginine residues), Amadori products, carbonyl content, Nε‐carboxymethyl lysine, and pentosidine using various physicochemical techniques. Moreover, fluorescence, absorbance as well as structural characteristics of glycated‐H2A were comprehensively investigated. Overall, this study demonstrates structural perturbation, formation of different intermediates, and AGEs that are believed to hamper the normal functioning of H2A histone, compromising the integrity of chromatin structures and function in secondary complications of diabetes. © 2014 IUBMB Life, 66(10):686–693, 2014